Corporate Governance and R&D Strategic Decision Making - Lee-Anne C Johennesse; I Gusti Agung Musa Budidarma Budidarma (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study seeks to develop understanding from the literature the important relationship between corporate governance mechanism especially board characteristics and R&D strategic decision making. Some board characteristics, such as board size and independence are positively associated with firm performance. Directors of different ethnic, cultural backgrounds and different nationalities stimulate a firm to improve or develop new products. Older directors are less risk-tolerant than younger ones and invest less in risky R&D investments. The effect of board size on performance is negative and significant, while it has a positive and significant impact on R&D investment. Therefore, board characteristics are the considerable factors in affecting the effective R&D strategic decision making.